Web Tv Streaming Design In The National University Information System: Web Tv Streaming Design In The National University Information System - Negara, Bagas Satria; Wahyuddin, M. Iwan; Nathasia, Novi Dian (Jurnal Mantik, 2020)
The development of information is currently growing rapidly, in the era of globalization television media (TV) is still the favorite choice for the public in getting an information as needed. With the advancement of technology in television and internet media, television broadcasting can not only be done on television sets but can also be broadcast via computer devices, laptops and cellphones with streaming technology based on websites and mobile. Streaming technology services are already widely used in website-based television stations in the user's need to facilitate online television broadcasts. But not only television stations that have streaming TV websites, every university has a streaming TV based website. To build a TV streaming website design, the WordPress blog engine application is used using the PHP programming language with the xampp application needed on the MariaDB database, as well as the local apache web server and YouTube Unas TV as a server in the streaming process. The final results of this study with the campus TV streaming website can make one of the electronic media that can inform campus activities streaming through the TV streaming website application, by using the internet students can view campus information media and can access it anywhere